Spontaneous remission in nephrotic syndrome relapses followed up for 6 months – A prospective cohort study - Kulkarni, Venu; Hanumanna, Anil Kumar; Kariyappa, Mallesh (Indian Journal of Child Health, 2024)
Background/Objectives: Nephrotic syndrome (NS) relapses are usually triggered by infections. Treatment of infections will be sufficient to cause resolution of symptoms. Our study aimed to determine frequency of spontaneous remission and its predictors. In addition, our main objective was to know the outcome of children after spontaneous remission of relapses for next 6 months.Materials and Methods: Prospective cohort study included all children who presented with NS relapses. Seventy-four children were enrolled from November 2016 to May 2018. Both, spontaneous remission YES and NO groups, were followed up for 6 month duration to study relapse free period and relapse rate.Results: About 53.7% relapses remitted spontaneously with only stress dose steroids. Duration of illness more than 24 months could predict likely chances of spontaneous remission RR 0.49, 95% CI 0.29–0.87 (p=0.003). Outcome parameters, that is, relapse free period and relapse rate were similar in both groups.Conclusion: About 50% of NS relapses will remit spontaneously with only stress dose of steroids and if required antibiotics. Waiting period of 1 week for clearance of infection and occurrence of spontaneous remission may be necessary before contemplating long steroid course for all relapses. Further studies are required with large sample size.